Accounting and governance in Africa – contributions and opportunities for further research. Issue 4 (6th November 2017) - Soobaroyen, Teerooven; Tsamenyi, Mathew; Sapra, Haresh
Abstract : Purpose: The purpose of this paper is to review and reflect on the contributions of the Journal of Accounting in Emerging Economies' special issue on accounting and governance in Africa. Design/methodology/approach: The themes and contributions from the accepted papers are identified and discussed in relation to prior research and potential for further studies. Findings: Key aspects of boards and corporate governance (CG), audit reporting and quality and government accounting practices are revealed as mechanisms which, in some cases, did have some consequences in the African context. However, in other cases, accounting or governance mechanisms appear to be at the periphery of organizational practice and exhibit little influence on decision making and accountability. Research limitations/implications: Whilst this paper does not provide a systematic review of the literature in the African context, it provides relating to special issue's contributions on CG, audit and government accounting on the continent. Originality/value: This special issue extends the burgeoning scholarship in African accounting and governance and provides directions and opportunities for future research.